Natural genetic variations from the tomato wild relative Solanum pennellii associated with domestication and drought resistance - Vicente, Mateus Henrique (2019)
Plant domestication led to a loss of genetic variation in many crops, due to the excessive emphasis in the selection of edible organs (root, leaf, stem or fruit) and the low selection pressure for other traits in the cultivated environment. This \'genetic erosion\' led to loss of alleles associated with resistance to environmental stresses, such as drought and salinity, which can in turn culminate in productivity losses. In tomato (Solanum lycopersicum L.), it is possible to tap into a reservoir of valuable genetic variation in its wild relatives. Identification of genetic variants associated with tomato domestication, and with stress resistance mechanisms which may have been lost during domestication, could be used to aid in breeding programs. In the present work, which was divided into two chapters, we carried out crosses between the wild species S. pennellii and the miniature tomato cultivar Micro-Tom (MT) and created two introgression lines (ILs), one with reduced organ size and another with increased drought tolerance. In the first chapter, we report the characterization and mapping of the IL denominated as Tiny organs and reduced yield (Toy). Toy harbors a S. pennellii genome segment on chromosome 7 and presents a considerable reduction in both vegetative (leaves) and reproductive (fruit) organs. We discuss how this could be a relevant trait underpinning tomato domestication. In the second chapter, we describe the drought tolerance mechanism of the IL Water Economy Locus in Lycopersicon (Well). Well harbors a S. pennellii genome segment on chromosome 1 and shows lower hydraulic conductance, possibly related to decreased xylem vessel size. The results shown suggest that this lower hydraulic conductance promotes a disturbance in the soil-plant-atmosphere hydraulic continuum leading to changes in stomatal behavior, which, in turn, are probably related to the delayed wilting of Well under conditions of water deficit.